2023
DOI: 10.1007/s12602-023-10095-1
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effect of Competitive Exclusion on the Transmission of ESBL E. coli in Chickens

Amera F. Ebrahem,
Azza S. El-Demerdash,
Rania M. Orady
et al.

Abstract: The extensive use of antimicrobial agents in broiler farms causes the emergence of antimicrobial resistance of E. coli producing severe economic losses to the poultry industry; therefore, monitoring the transmission of ESBL E. coli is of great significance throughout broiler farms. For this reason, we investigated the efficiency of competitive exclusion (CE) products to control the excretion and transmission of ESBL-producing E. coli in broiler chickens. Three hundred samples from 100 broiler chickens were scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Several recent studies have reported the emergence of multidrug-resistant bacterial pathogens from different origins necessitating proper use of antibiotics. Routine application of antimicrobial susceptibility testing is necessary to detect the antibiotic of choice and to screen for the emerging MDR strains (El-Demerdash et al 2018 ; Algammal et al 2021 , 2022a , 2023 ; Ebrahem et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have reported the emergence of multidrug-resistant bacterial pathogens from different origins necessitating proper use of antibiotics. Routine application of antimicrobial susceptibility testing is necessary to detect the antibiotic of choice and to screen for the emerging MDR strains (El-Demerdash et al 2018 ; Algammal et al 2021 , 2022a , 2023 ; Ebrahem et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%